Use of Mesothelial Cells and Biological Matrices for Tissue Engineering of Simple Epithelium Surrogates - Lachaud, Christian Claude; Rodriguez-Campins, Berta; Hmadcha, Abdelkrim; Soria, Bernat (Frontiers in Bioengineering and Biotechnology, 2015)
Tissue-engineering technologies have progressed rapidly through last decades resulting in the manufacture of quite complex bioartificial tissues with potential use for human organ and tissue regeneration. The manufacture of avascular monolayered tissues such as simple squamous epithelia was initiated a few decades ago and is attracting increasing interest. Their relative morphostructural simplicity makes of their biomimetization a goal, which is currently accessible. The mesothelium is a simple squamous epithelium in nature and is the monolayered tissue lining the walls of large celomic cavities (peritoneal, pericardial, and pleural) and internal organs housed inside. Interestingly, mesothelial cells can be harvested in clinically relevant numbers from several anatomical sources and not less important, they also display high transdifferentiation capacities and are low immunogenic characteristics, which endow these cells with therapeutic interest. Their combination with a suitable scaffold (biocompatible, degradable, and non-immunogenic) may allow the manufacture of tailored serosal membranes biomimetics with potential spanning a wide range of therapeutic applications, principally for the regeneration of simple squamous-like epithelia such as the visceral and parietal mesothelium vascular endothelium and corneal endothelium among others. Herein, we review recent research progresses in mesothelial cells biology and their clinical sources. We make a particular emphasis on reviewing the different types of biological scaffolds suitable for the manufacture of serosal mesothelial membranes biomimetics. Finally, we also review progresses made in mesothelial cells-based therapeutic applications and propose some possible future directions.